2020
DOI: 10.1029/2019jd030528
|View full text |Cite
|
Sign up to set email alerts
|

Constraining Fossil Fuel CO2 Emissions From Urban Area Using OCO‐2 Observations of Total Column CO2

Abstract: Satellite observations of the total column dry-air CO 2 (X CO2 ) are expected to support the quantification and monitoring of fossil fuel CO 2 (ffCO 2 ) emissions from urban areas. We evaluate the utility of the Orbiting Carbon Observatory 2 (OCO-2) X CO2 retrievals to optimize whole-city emissions, using a Bayesian inversion system and high-resolution transport modeling. The uncertainties of constrained emissions related to transport model, satellite measurements, and local biospheric fluxes are quantified. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 105 publications
2
52
0
Order By: Relevance
“…Broquet et al (2018) showed that systematic error could hamper the ability of the inversion system to reduce the errors in the emissions estimates. Thirdly, we neglect the impact of uncertainties in diffuse fossil fuel CO 2 emissions (outside clumps) and non-fossil CO 2 fluxes (within and outside clumps), the latter including net ecosystem exchange (NEE) from the terrestrial biosphere, the CO 2 emitted by the burning of biofuel, the respiration 5826 Y. Wang et al: Potential of satellite observations to constrain CO 2 emissions from humans and animals (Ciais et al, 2020), and the net CO 2 fluxes between the atmosphere and ocean. For example, the signals from terrestrial NEE can be strong during the growing season, and the signals from ocean CO 2 fluxes may have a critical impact on the overall XCO 2 patterns in proximity to coastlines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Broquet et al (2018) showed that systematic error could hamper the ability of the inversion system to reduce the errors in the emissions estimates. Thirdly, we neglect the impact of uncertainties in diffuse fossil fuel CO 2 emissions (outside clumps) and non-fossil CO 2 fluxes (within and outside clumps), the latter including net ecosystem exchange (NEE) from the terrestrial biosphere, the CO 2 emitted by the burning of biofuel, the respiration 5826 Y. Wang et al: Potential of satellite observations to constrain CO 2 emissions from humans and animals (Ciais et al, 2020), and the net CO 2 fluxes between the atmosphere and ocean. For example, the signals from terrestrial NEE can be strong during the growing season, and the signals from ocean CO 2 fluxes may have a critical impact on the overall XCO 2 patterns in proximity to coastlines.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the signals from terrestrial NEE can be strong during the growing season, and the signals from ocean CO 2 fluxes may have a critical impact on the overall XCO 2 patterns in proximity to coastlines. In principle, the signals of diffuse fossil fuel CO 2 emissions and non-fossil CO 2 fluxes outside the clumps can be potentially filtered by removing the local background XCO 2 field to extract plumes generated only by emissions from clumps (Kuhlmann et al, 2019;Reuter et al, 2019;Ye et al, 2020;Zheng et al, 2020). The nonfossil CO 2 fluxes within clumps vary from clump to clump and could contribute a non-negligible fraction of the total CO 2 fluxes in many clumps (Bréon et al, 2015;Ciais et al, 2020;Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subsequent study indicated that the WRF‐VPRM was able to capture the atmospheric CO 2 temporal and spatial distributions and performed better than other global models in simulating diurnal variability of atmospheric CO 2 concentration field (Ahmadov et al, 2009). In the past decade, the application and evaluation of WRF‐VPRM mainly focused on North America (Feng et al, 2016; Hu et al, 2019b, 2020; Park et al, 2018; Ye et al, 2017) and Europe (Pillai et al, 2011). The model performances remain unknown in Asia including China due to the lack of observations, as well as model uncertainties due to uncertainties of VPRM parameters in the region (Dayalu et al, 2018; Hilton et al, 2013; Liu et al, 2015; Zhang et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Diao et al (2015) used WRF‐VPRM to investigate the spatiotemporal characteristics of NEE and surface CO 2 concentrations over the Yangtze River Delta region in China for 5 days, from 28 July to 2 August 2010. Ye et al (2017) assessed the biotic contribution to the XCO 2 enhancements during two short episodes (12–15 January and 1–4 August 2015) over the Pearl River Delta metropolitan region in China using the WRF‐VPRM. However, these short‐term (a few days) simulations could not reveal long‐term variations of CO 2 fluxes/concentrations.…”
Section: Introductionmentioning
confidence: 99%